Olig2 regulates Sox10 expression in oligodendrocyte precursors through an evolutionary conserved distal enhancer - Küspert, Melanie (Oxford University Press, 2011)
The HMG-domain transcription factor Sox10 is expressed throughout oligodendrocyte development and is an important component of the transcriptional regulatory network in these myelin-forming CNS glia. Of the known Sox10 regulatory regions, only the evolutionary conserved U2 enhancer in the distal 5′-flank of the Sox10 gene exhibits oligodendroglial activity. We found that U2 was active in oligodendrocyte precursors, but not in mature oligodendrocytes. U2 activity also did not mediate the initial Sox10 induction after specification arguing that Sox10 expression during oligodendroglial development depends on the activity of multiple regulatory regions. The oligodendroglial bHLH transcription factor Olig2, but not the closely related Olig1 efficiently activated the U2 enhancer. Olig2 bound U2 directly at several sites including a highly conserved one in the U2 core. Inactivation of this site abolished the oligodendroglial activity of U2 in vivo. In contrast to Olig2, the homeodomain transcription factor Nkx6.2 repressed U2 activity. Repression may involve recruitment of Nkx6.2 to U2 and inactivation of Olig2 and other activators by protein–protein interactions. Considering the selective expression of Nkx6.2 at the time of specification and in differentiated oligodendrocytes, Nkx6.2 may be involved in limiting U2 activity to the precursor stage during oligodendrocyte development.